Deficiency of Thioredoxin Binding Protein-2 (TBP-2) Enhances TGF-β Signaling and Promotes Epithelial to Mesenchymal Transition - Masaki, So (Public Library of Science, 2012)
BACKGROUND: Transforming growth factor beta (TGF-β) has critical roles in regulating cell growth, differentiation, apoptosis, invasion and epithelial-mesenchymal transition (EMT) of various cancer cells. TGF-β-induced EMT is an important step during carcinoma progression to invasion state. Thioredoxin binding protein-2 (TBP-2, also called Txnip or VDUP1) is downregulated in various types of human cancer, and its deficiency results in the earlier onset of cancer. However, it remains unclear how TBP-2 suppresses the invasion and metastasis of cancer. PRINCIPAL FINDINGS: In this study, we demonstrated that TBP-2 deficiency increases the transcriptional activity in response to TGF-β and also enhances TGF-β-induced Smad2 phosphorylation levels. Knockdown of TBP-2 augmented the TGF-β-responsive expression of Snail and Slug, transcriptional factors related to TGF-β-mediated induction of EMT, and promoted TGF-β-induced spindle-like morphology consistent with the depletion of E-Cadherin in A549 cells. CONCLUSIONS/SIGNIFICANCE: Our results indicate that TBP-2 deficiency enhances TGF-β signaling and promotes TGF-β-induced EMT. The control of TGF-β-induced EMT is critical for the inhibition of the invasion and metastasis. Thus TBP-2, as a novel regulatory molecule of TGF-β signaling, is likely to be a prognostic indicator or a potential therapeutic target for preventing tumor progression.